2020
DOI: 10.1002/lary.29219
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Protective Effects of Statins in Chronic Rhinosinusitis: A Case–Control Study

Abstract: Objectives/Hypothesis To determine the potential protective effect of prior statin use on the subsequent diagnosis of chronic rhinosinusitis (CRS). Study Design Retrospective, case‐control. Methods Electronic medical records for all patients seen in the otolaryngology clinic in 2019 and receiving a diagnosis of CRS were reviewed for the presence or absence of active prior statin use within 365 days of the visit. Similarly, prior statin use in a control group of patients without any diagnosis of CRS was also de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Findings of reduced symp-tom severity among statin users may help to explain, in part, results of population-based studies that reported the protective effects of statin use against a diagnosis of CRS. 2,3 Statin users had a higher prevalence of normosmia and, on average, higher individual T, D, and I scores; however, differences with non-statin users were not statistically significant in comparison. The lack of significance may be partially due to the relatively limited sample size of statin users.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…Findings of reduced symp-tom severity among statin users may help to explain, in part, results of population-based studies that reported the protective effects of statin use against a diagnosis of CRS. 2,3 Statin users had a higher prevalence of normosmia and, on average, higher individual T, D, and I scores; however, differences with non-statin users were not statistically significant in comparison. The lack of significance may be partially due to the relatively limited sample size of statin users.…”
mentioning
confidence: 79%
“…Statins block the mevalonate pathway and prevent activation G proteins—a mechanism that may have a role in the management of airway inflammation 1 . Accordingly, multiple population‐based studies suggest that statins may be protective against development of CRS, whereas others have noted a potential detrimental effect, with concerns that statins may propogate some atopic diseases 2–4 . In vitro studies of human airway epithelial cells have demonstrated that expression of the inflammatory mediators C‐C motif chemokine ligand‐5 (CCL‐5), CCL‐11, interleukin‐5 (IL‐5), and IL‐13RA are inhibited by statin exposure 1 .…”
Section: Cofactors Statin Use (N = 34) No Statin Use (N = 135) Test S...mentioning
confidence: 99%
See 2 more Smart Citations
“…6 Gilani et al performed a similar study in a single institution and found similar results. 5 Rimmer et al investigated the difference in subjective (SNOT-22 scores) and objective measures (LK, LM CT, and olfactory function) between CRS patients on statins and those not on statins. They found a significant difference in the total SNOT-22 score, as well as the rhinologic, ear/face, and psychological subdomains (all lower in statin users) of the SNOT-22 on univariable analysis.…”
Section: Discussionmentioning
confidence: 99%